2022
DOI: 10.3390/ani12213026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zearalenone-Induced Ferroptosis on Mice Spermatogenesis

Abstract: Male reproductive health is critically worsening around the world. It has been reported that the mycotoxin ZEA causes reproductive toxicity to domestic animals and affects spermatogenesis, thereby inhibiting male reproductive function. Ferroptosis is a newly identified type of programmed cell death that is different from apoptosis and it depends on iron accumulation and lipid peroxidation. Whether ferroptosis is linked to ZEA’s detrimental effect on spermatogenesis needs to be further explored. This study clar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Patulin (PAT) exposure reduced the downregulation and upregulation of SLC7A11, GPX4, and FTH1 expressions in mouse kidney . After administering ZEA orally to mice, it was found that ZEA inhibited the protein expressions of SLC7A11 and GPX4 and led to the accumulation of lipid peroxides and iron in the testes, which is similar to the present results. DFO is an iron-chelating agent that inhibits ferroptosis by chelating iron .…”
Section: Discussionmentioning
confidence: 99%
“…Patulin (PAT) exposure reduced the downregulation and upregulation of SLC7A11, GPX4, and FTH1 expressions in mouse kidney . After administering ZEA orally to mice, it was found that ZEA inhibited the protein expressions of SLC7A11 and GPX4 and led to the accumulation of lipid peroxides and iron in the testes, which is similar to the present results. DFO is an iron-chelating agent that inhibits ferroptosis by chelating iron .…”
Section: Discussionmentioning
confidence: 99%
“…Microscopic examination of the testicular seminiferous epithelial tissue in ZEN-exposed mice depicted structural abnormalities such as loose, hollow, reduced sperm count within seminiferous tubules and irregular arrangement of germ cells, indicative of ZEN-induced damage to testicular integrity. Recent reports by Li et al [ 32 ] suggested that ZEN could influence spermatogenesis through ferroptosis, potentially caused by iron accumulation in testicular tissue, leading to irregular germ cell arrangements in the testes. However, pretreatment with RUT exhibited notable differences in the reproductive epithelium, showing increased structural integrity and more uniform cell arrangements.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the above-mentioned classical cell death pathway, we wondered if ZEA could alter other aspects that are essential for cell survival, such as the transport of metal ions. Evidence has shown that ZEA can increase the Fe 2+ and Fe 3+ concentration on mice spermatogenesis, leading to a higher ferroptosis level [30]. T-2 toxin promoted ferroptosis by inducing lipid ROS and decreased the expression of solute carrier family 7 member 11 (SLC7A11) [31].…”
Section: Discussionmentioning
confidence: 99%